Isolation of Cellulose from Wheat Straw Using Alkaline Hydrogen Peroxide and Acidified Sodium Chlorite Treatments: Comparison of Yield and Properties. (25th February 2020) - Qasim, Umair; Ali, Zulfiqar; Nazir, Muhammad Shahid; Ul Hassan, Sadaf; Rafiq, Sikander; Jamil, Farrukh; Al-Muhtaseb, Ala'a H.; Ali, Muzaffar; Khan Niazi, Muhammad Bilal; Ahmad, Nasir M.; Ullah, Sami; Mukhtar, Ahmad; et al.
Abstract : Environmental concerns due to excessive use of synthetic or petroleum-based materials have encouraged scientists to develop novel, sustainable, and multifunctional material using abundant lignocellulosic biomass. In this work, a study was conducted on the isolation of cellulose from wheat straw using two different methods: acidified sodium chlorite and alkaline hydrogen peroxide. A comparative study was carried out based on the yield and properties of extracted cellulose. The final product (after treatments) was characterized by Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), and thermogravimetric analysis (TGA) for the identification of properties. Both the treatments isolated pure white color cellulose. However, the yield of cellulose isolated through acidified sodium chlorite treatment (81.4%) was higher than alkaline hydrogen peroxide treatment (79%). Moreover, no huge difference was observed in the crystallinity and thermal properties of extracted cellulose.